Fabrication and Performance of a Silver Nanowire Silk Conductive Fabric - Chen, Xinpeng (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this work, silk was selected as the substrate, and formic acid was utilized to create a rough texture on the silk. The conductive fabrics made from AgNWs and silk were created by applying multiple layers of silver nanowire dispersion onto the textured silk fabrics (SFs). The silk was immersed in a dispersion containing polydopamine (PDA), sericin (SE), tannic acid (TA), and silver nanowire under specific temperature conditions. After being cured at 120 °C, the three silver nanowire/silk fabrics (AgNWs/SFs), PDA/AgNWs/SF, SE/AgNWs/SF, and TA/AgNWs/SF, exhibited square resistances of 7.37, 540, and 200 Ω/sq, respectively. The method used to prepare the AgNW conductive SF is straightforward, resulting in fabrics that possess excellent thermal stability and resistance to washing. These fabrics also exhibit a range of useful properties, including conductivity, electrothermal capabilities, electrochemical functionality, human body sensing, hydrophobicity, and antimicrobial properties. These characteristics make them highly promising for various applications, such as human body motion detection, electronic textiles, electrothermal textiles, and antimicrobial applications